2010
DOI: 10.1182/blood-2009-10-250779
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of SHOC2, a novel gene for Noonan-like syndrome, in JMML

Abstract: Cordeddu et al recently reported the discovery of a specific SHOC2 gene mutation underlying a variant of the neuro-cardio-facio-cutaneous (NCFC) syndrome family. 1 The common denominator of mutations associated with this group of disorders is their involvement in the dysregulation of the Ras-mitogen-activated protein kinase (MAPK) pathway. 2 Mutant SHOC2 undergoes aberrant N-myristoylation that results in constitutive membrane targeting. This in turn is thought to sustain RAF1-stimulated MAPK activation. 1 The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…We did not detect any significant signals for either GFAP or MBP in the neural tube of the (E12.5 þ 3DIV) embryos. The importance of Sur8 in neuronal development may be related to the recent reports of Sur8 defects in Noonan syndrome, which accompanies mental retardation [31][32]. Sur8's potentiality as a neural stem cell factor is also shown in its role in inhibition of differentiation and activation of proliferation in the present study by both Sur8 overexpression and knockdown experiments using various experimental approaches.…”
Section: Discussionsupporting
confidence: 63%
“…We did not detect any significant signals for either GFAP or MBP in the neural tube of the (E12.5 þ 3DIV) embryos. The importance of Sur8 in neuronal development may be related to the recent reports of Sur8 defects in Noonan syndrome, which accompanies mental retardation [31][32]. Sur8's potentiality as a neural stem cell factor is also shown in its role in inhibition of differentiation and activation of proliferation in the present study by both Sur8 overexpression and knockdown experiments using various experimental approaches.…”
Section: Discussionsupporting
confidence: 63%
“…The role of SHOC2 in malignancies still remains to be elucidated. Mutation analysis of SHOC2 in JMML revealed no evidence of leukemogenic SHOC2 involvement [Flotho et al, 2010]. However, additional studies will be required to determine the contribution of SHOC2 in malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that no SHOC2 mutations were identified in 22 patients with juvenile myelomonocytic leukemia. 27 It is possible that the absence of mutation was due to the relatively small sample size. Alternatively, the gain of function of SHOC2 might not have leukemogenic potential, and other factors such as aberrant cytokine production may be associated with leukocytosis.…”
Section: Discussionmentioning
confidence: 99%